Size dependent allocation to vegetative and reproductive organs of the orchid Lankesterella ceracifolia (Spiranthinae) - Mantovani, André (2022)
How functional organ traits vary with increasing plant size reveals the strategies of plants to acquire, store and utilize resources that ensure vegetative growth and reproduction. Plant size can influence fitness; thus, the relationships of organ traits should be evaluated together with reproductive allocation, but this is rarely the case. The relationship among plant size, functional organ traits (number and size of roots, leaves and flowers, and scape size), and dry mass partitioning was analyzed intraspecifically using 35 reproductive individuals of the epiphytic orchid Lankesterella ceracifolia. The relationships between vegetative and reproductive organ traits were evaluated using different regression models. Size-dependent allocation to reproduction was evaluated through reproductive versus vegetative (RV) regressions for the entire inflorescence and separately for scape and flowers. The four regression models included simple (slope only), linear (slope and intercept), allometric (without intercept), and non-linear (allometric with intercept), were fitted to RV and compared via a log likelihood-ratio test. Preferential allocation to leaves instead of roots influenced how rosette frontal area changed with increasing plant size. Flower dry mass represented 70% of the inflorescence dry mass, an unusual result as scape dry mass generally represents most of the reproductive structure in plants. The allometric model was suitable for the entire inflorescence or only the scape, while the isometric model was best for flowers. Dry mass investment in the scape influenced the final reproductive allometry found for the orchid L. ceracifolia.